Review of the leafhopper genus Drabescus Stål (Hemiptera: Cicadellidae: Deltocephalinae) in the Indian subcontinent with description of one new species - Viraktamath, C.a.; Webb, M. D.; Yeshwanth, H. M. (Zootaxa, 2022)
The leafhopper genus Drabescus Stål is reviewed for the Indian subcontinent with one new species described, D. austroindicus sp. nov. (India: Tamil Nadu). A checklist and key to the species from the Indian subcontinent are given.